Differences in Gross Motor Development among Early School Children: Comparison on Team and Individual Sports - Mehamad, Mohd Fahme Zamzam Bin; Abdullah, Borhannuddin Bin; Samsuddin, Shamsulariffin (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
This study aimed to determine the level of gross motor development of children aged eight to ten years involved in individual (I) and team (T) sports by using the Tests of Gross Motor Development-2 (TGMD-2) method. This study is an ex-post factor involving 360 children in their early schooling stages (M = 180, F = 180). The study involved 2 types of sports: individually (Athletics = 60, Badminton = 60, Taekwondo = 60) and team (Handball = 60, Hockey = 60, Basketball = 60). Descriptive analysis has shown the level of performance for individual sports AEL (M = 8.24, SD = 1.02, DR = Average), AEM (M = 7.16, SD = 0.92, DR = Below Average) and GMDQ (M = 87.87, SD = 5.4, DR = Below Average). For team sports, the age equivalence levels of AEL (M = 8.05, SD = 1.23, DR = Average), AEM (M = 7.84, SD = 1.07, DR = Below Average) and GMDQ (M = 90.02, SD = 6.57, DR = Below Average). There was a significant difference for individual and team sports on the AEL score t (358) = 1.64, p = 0.00. While there was no significant difference for individual and team sports on the AEM score t (358) =-6.45, p = 0.27 and GMDQ t (358) =-3.39, p = 0.06. MANOVA analysis showed that there were significant differences for AEL, AEM and GMDQ scores for athletics, badminton, taekwondo, handball, hockey, and basketball with [F (15,972.12) = 11.82, p <0.001, eta squared = 0.14]. Individual sport types had an AEL age delay of -1.27 years and an AEM of -2.15 years in contrast to team sports with an AEL age delay of -1.25 years and an AEM of only -1.37 years. ANCOVA analysis showed that gender and age could influence the level of gross motor development of individual and team sports. Implementing the gross motor development test provides knowledge and information to teachers and coaches to know athletes’ gross motor acquisition. Teachers and coaches could also design a training program to help athletes strengthen their gross motor development and improve their athletic performance.